2022
DOI: 10.3390/inorganics10080118
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Heterometallic [Zn2Ca] Pinwheel Array Stabilized by Amide-Amide Synthons

Abstract: The rational design of heterometallic compounds bearing s-block metal ions have been a difficult task for chemists owing to their lack of preferential geometries. However, some strategies, such as the design of coordinating pockets with different sizes and/or donor atoms, have offered great results. In this work, this strategy has been tested using Ca(II) as an s-block metal ion and a compound previously obtained by our group with the formula [Zn3(μ-ACA)6(4-phpy)2], which contains tetrahedral N,O- and octahedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…To date, only one dihydrate and one cocrystal have been reported. The dihydrate structure connected the HACA molecules through masked synthons of water clusters supported by acid···amide interactions, , whereas the cocrystal contained 2-pyridone (Pdon), presenting Pdon···acid and amide···amide synthons . However, previous studies performed in the group with coordination compounds suggested a tendency of the HACA molecules toward being ordered by amide···amide patterns, leading to supramolecular chains or cycles depending on the synthetic conditions. …”
Section: Introductionmentioning
confidence: 99%
“…To date, only one dihydrate and one cocrystal have been reported. The dihydrate structure connected the HACA molecules through masked synthons of water clusters supported by acid···amide interactions, , whereas the cocrystal contained 2-pyridone (Pdon), presenting Pdon···acid and amide···amide synthons . However, previous studies performed in the group with coordination compounds suggested a tendency of the HACA molecules toward being ordered by amide···amide patterns, leading to supramolecular chains or cycles depending on the synthetic conditions. …”
Section: Introductionmentioning
confidence: 99%